The impact of COVID-19 on a South African pediatric cardiac service: implications and insights into service capacity - Thomas Aldersley; Thomas Aldersley; Andre Brooks; Andre Brooks; Andre Brooks; Paul Human; Paul Human; John Lawrenson; John Lawrenson; John Lawrenson; John Lawrenson; George Comitis; et al. (Frontiers Media S.A., 2023)
Background and ObjectivesThe Western Cape public pediatric cardiac service is under-resourced. COVID-19 regulations are likely to have long-term effects on patient care but may provide insight into service capacity requirements. As such, we aimed to quantify the impact of COVID-19 regulations on this service.MethodsAn uncontrolled retrospective pre-post study of all presenting patients over two, one-year periods; the pre-COVID-19 period (01/03/2019-29/02/2020) and the peri-COVID-19 period (01/03/2020-28/02/2021).ResultsAdmissions decreased by 39% (624 to 378) and cardiac surgeries decreased by 29% (293 to 208) in the peri-COVID-19 period, with an increase in urgent cases (PR:5.99, 95%CI:3.58-10.02, p < 0.001). Age at surgery was lower in the peri-COVID-19 period, 7.2 (2.4-20.4) vs. 10.8 (4.8-49.2) months (p < 0.05), likewise, age at surgery for transposition of the great arteries (TGA) was lower peri-COVID-19, 15 (IQR:11.2-25.5) vs. 46 (IQR:11-62.5) days (p < 0.05). Length of stay 6 (IQR:2-14) vs. 3 days (IQR:1-9) (p < 0.001), complications (PR:1.21, 95%CI:1.01-1.43, p < 0.05), and age-adjusted delayed-sternal-closure rates (PR:3.20, 95%CI:1.09-9.33, p < 0.05) increased peri-COVID-19.ConclusionCardiac procedures were significantly reduced in the peri-COVID-19 period which will have implications on an overburdened service and ultimately, patient outcomes. COVID-19 restrictions on elective procedures freed capacity for urgent cases, demonstrated by the absolute increase in urgent cases and significant decrease in age at TGA-surgery. This facilitated intervention at the point of physiological need, albeit at the expense of elective procedures, and also revealed insights into capacity requirements of the Western Cape. These data emphasize the need for an informed strategy to increase capacity and reduce backlog whilst ensuring minimal morbidity and mortality.Graphical Abstract